2004
DOI: 10.1088/0953-8984/16/21/009
|View full text |Cite
|
Sign up to set email alerts
|

Polaron crossover in molecular solids

Abstract: An analytical variational method is applied to the molecular Holstein Hamiltonian in which the dispersive features of the dimension dependent phonon spectrum are taken into account by a force constant approach. The crossover between a large and a small size polaron is monitored, in one, two and three dimensions and for different values of the adiabatic parameter, through the behavior of the effective mass as a function of the electron-phonon coupling. By increasing the strength of the inter-molecular forces th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…The third and fourth terms of Eq.1 represent the electron-phonon interaction and phonon harmonic energy, respectively. These terms may be written in the momentum space defined by the phonon creation operators: b † q = (1/ √ N ) i b † i e iq.R i and the corresponding annihilation operators, where N is the number of sites in the system 5,6,14 . It can be easily shown that the in-phase (q = 0) phonon mode does not couple with the electron dynamics but with the total number of electrons of the system.…”
Section: Formalismmentioning
confidence: 99%
“…The third and fourth terms of Eq.1 represent the electron-phonon interaction and phonon harmonic energy, respectively. These terms may be written in the momentum space defined by the phonon creation operators: b † q = (1/ √ N ) i b † i e iq.R i and the corresponding annihilation operators, where N is the number of sites in the system 5,6,14 . It can be easily shown that the in-phase (q = 0) phonon mode does not couple with the electron dynamics but with the total number of electrons of the system.…”
Section: Formalismmentioning
confidence: 99%
“…This effect is more pronounced in higher dimensionality. 13 On the other hand, the dispersive nature of the phonon spectrum is recognized as a fundamental feature of the Holstein model as it allows for finite values of the electronic site jump probability while a dispersionless model would lead to un-physical divergences. 12,14 Also ground state properties such as electron bandwidth and effective mass are more properly evaluated versus dimensionality within a dispersive model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, for λ = 1.1λ c the diagonal m d (k x = k y ) and transverse m t (k x = −k y ) masses for the local EPI are m d = 200 and m t = 88 whereas for nonlocal EPI the masses m d = 20 and m t = 10 are considerably lighter. Lighter mass for nonlocal EPI [98,195,[260][261][262][263][264][265] or dispersive phonons [266][267][268][269] was observed in many models.…”
Section: Nonlocal Epimentioning
confidence: 99%